Effects of temperature and of the addition of accelerating and retarding agents on the kinetics of hydration of tricalcium silicate - Vollet, Dimas R. [UNESP]; Craievich, Aldo F. (American Chemical Society (ACS), 2000)
The formation of calcium silicate hydrates (C-S-H) during the hydration of tricalcium silicate (C3S) in pure water and in water solutions containing 1% CaCl2 (accelerator) and 0.01% saccharose (retarder) was studied by small-angle X-ray scattering (SAXS). SAXS measurements were performed under isothermal conditions within the temperature range 25 °C T < 52 °C. The experimental results indicate that the time variation of the mass fraction of the C-S-H product phase, α(f), can be fitted, under all conditions of paste setting, by Avrami equation, α(t) = 1 -exp(-(kt)′), k being a rate parameter and n an exponent depending on the characteristics of the transformation. The parameter n is approximately equal to 2 for hydration of C^S in pure water. Depending on temperature, n varies from 2 to 2.65 for hydration in the presence of CaC^ and saccharose. The value n = 2 is theoretically expected for lateral growth of thin C-S-H plates of constant thickness. The time dependence of SAXS intensity indicates that the transformed phase (C-S-H) consists of colloidal particles in early stages of hydration, evolving by two-dimensional growth toward a disordered lamellar structure composed of very thin plates. The activation energy ΔE for the growth of C-S-H phase was determined from the time dependence of X-ray scattering intensity. These data were obtained by in situ measurements at different temperatures of hydration. The values of ΔE are 37.7, 49.4, and 44.3 kJ/mol for hydration in pure water and in water solutions containing CaCl2 and saccharose, respectively. © 2000 American Chemical Society.
Keywords: Activation energy; Agents; Hydration; Phase transitions; Reaction kinetics; Silicates; Thermal effects; X ray scattering; Small angle X ray scattering (SAXS); Tricalcium silicate; Calcium compounds